P4 Designing and implementing a bespoke multidisciplinary paediatric emergency refresher course in an adult tertiary hospital. (3rd November 2019) - Miller, Tamryn; Grice, Julie; Wharton, Tim; Mercer, Simon
Abstract : Background: Aintree Hospital is an adult tertiary centre providing care to 330, 000 patients. There is a paediatric centre of excellence located 4 miles away however, despite its close proximity, acutely unwell children still present to the Emergency Department. We noted that the clinical teams managing these children may not have had recent paediatric training or practical experience, and there was a need to increase knowledge, confidence and team working in managing these challenging cases. Summary of work: We distributed a survey to identify 1) training gaps 2) previous issues faced when managing paediatrics in the emergency department and 3) difficult cases clinicians attending wanted to simulate, in order to customise the course and improve knowledge retention¹. We sought advice from the radiology department and paediatric transfer service regarding which facilities are feasible in our location. Finally, we collaborated with the children's hospital to devise and install a new paediatric trolley in the emergency department, which will be tested during the course. Summary of results: The survey revealed: Equipment and staff training were identified as obstacles hindering optimal management. 57% of respondents were up to date with APLS. 28% had managed a paediatric case in the emergency department within the last 3 years, 43% had not been involved in any cases. 29% of anaesthetists had anaesthetised a child within the last year, 57% within 2 years and 86% within 3 years. One respondent hadn't anaesthetised a child in over 10 years. Common themes requested for scenarios included: sepsis, status epilepticus, trauma and cases using very young children/neonates to provide challenging training. Discussion and conclusions: With guidance from the survey, we have designed paediatric scenarios that could potentially present to an adult hospital and involve the multidisciplinary emergency team. In order to improve patient safety, scenarios include the use of the paediatric trolley to promote familiarity and identify latent errors for evaluation². It has been important to involve the stakeholders in the design of this course as they have markedly influenced the direction of flow of the simulated cases. We are piloting this course in June 2019 and will collect feedback from delegates attending as well as faculty, which includes our radiology and paediatric transfer service colleagues who are attending to contribute to debrief discussions. We will repeat this course 3 times yearly and modify it based on feedback and new cases that present to our hospital. References: McQueen AA, Mitchell DL, Joseph-Griffin MA, 2011. 'Not Little Adults': Pediatric Considerations in Medical Simulation. 780–788. Available from: http://www.sciencedirect.com/science/article/pii/S0011502911002197. EICH, C., TIMMERMANN, A., RUSSO, S. G., NICKEL, E. A., MCFADZEAN, J., ROWNEY, D. and SCHWARZ, S. K. W., 2007. Simulator-based training in paediatric anaesthesia and emergency medicine – Thrills, skills and attitudes. British Journal of Anaesthesia . 98 (4), pp. 417–419. Available from: https://www.sciencedirect.com/science/article/pii/S0007091217354909.